Development of the Emotional Intelligence Scale - Mehta, Sandhya; Singh, Ms.Namrata (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This paper describes the development of the Emotional intelligence Scale EI(PcSc)scale as tested on pilot study of 200 respondents. The EI(PcSc)scale is a self-report questionnaire comprising two parts: personal competence and social competence that measures six facets of emotional intelligence in the workplace. Estimates of internal consistency for the subscales ranged from .78 to .91.